APLIKASI PENCEGAH PENIPUAN JUAL BELI AKUN MOBILE LEGENDS BERBASIS MOBILE MENGGUNAKAN FRAMEWORK FLUTTER - Agil Fajar Dwi Prasetyo; Ade Eviyanti; Metatia Intan Mauliana (Politeknik Bisnis Indonesia, 2024)
The internet is a phenomenon in today's era, serving not only as a medium for information sharing but also permeating the realm of online gaming, particularly Mobile Legends. This online game, playable even on low specifications, offers not only pure entertainment but also a potential avenue for trade. However, this situation can give rise to fraudulent activities due to Mobile Legends'